Digital Curation in the postmodern social perspective: curatorial facets, concepts and participatory techniques - da Silva Batista, Lucineia [UNESP]; de Oliveira Souza, Gabriela [UNESP]; Jorente, Maria José Vicentini [UNESP] (FapUNIFESP (SciELO), 2023)
Information and Communication Technologies transform the spaces for presenting cultural heritage information and communication from brick-and-mortar spaces into hybrid environments: both on-site and digital-virtual. This transformation demands a more specific Digital Curation on the Web 2.0 context, platform on which participatory approaches emerge in the curatorial process, such as Social, Collective and Citizen Curations, which use crowdsourcing and storytelling. In this scenario, this article questions the difference between Digital Curation and other participatory curations which have emerged in postmodernity. The objective was to explore the Digital Curation facets in the participatory approach in the scope of Information Science. The scientific relevance of the paper was justified by the need for stakeholders’ participation in the curation of cultural contents and the necessary approach by Information Science. The methodology was qualitative in nature, theoretical and exploratory. The theoretical research was carried out on the proposed themes, and their similarities and differences were explored. Digital Curation expands by presenting new curatorial facets - Social, Citizen and Collective-, which present different levels of social involvement and can converge with each other, according to the objective of the proposed curation project. Crowdsourcing and storytelling techniques are used for the curatorial process with a participatory approach.
Curadoria Digital na perspectiva social pós-moderna: facetas curatoriais, conceitos e técnicas participativas
Keywords: Crowdsourcing; Digital Curation; Hybrid Cultural Spaces; Participatory Approach; Storytelling